The Effect of Application-Based Augmented Reality Technology as Learning Media on the Learning Outcomes of MAN 1 Padangsidimpuan Plus Riset Students (Indo-MathEdu Intellectuals Journal, 2025)
This study was conducted to determine the use of application-based augmented reality technology as a learning medium to influence student learning outcomes at MAN 1 Padangsidimpuan Plus Research. This research is a quantitative research using experimental research methods. The experiment used is the use of application-based augmented reality technology as a learning medium which will be carried out in class XI MAN 1 Padangsidimpuan Plus Research. The data collection techniques used in this study used test, questionnaire, and observation instruments. Data analysis was carried out using simple linear regression analysis. The results of the research that will be obtained are in the form of the significance of the hypothesis test on the learning outcomes of students in the experimental class after receiving the treatment of using application-based augmented reality technology as a learning medium. Based on the results of a simple linear regression analysis test using IBM SPSS Statistics 25 software, the significance value obtained was 0.026 < 0.05. That there was an influence of the use of application-based augmented reality technology as a learning medium on the learning outcomes of MAN 1 Padangsidimpuan Plus Research students